Sulfate resistance and phase composition of shotcrete. (March 2021) - Kaufmann, Josef; Loser, Roman; Winnefeld, Frank; Leemann, Andreas
Highlights: Analysis of the chemical phase composition of shotcrete. Testing the sulfate resistance of shotcrete and comparison with conventional concrete. Relating the microstructure, transport properties, porosity and phase composition of shotcrete to its sulfate resistance. Effect of different set accelerators and cements. Abstract: Shotcrete is often in direct contact with groundwater containing sulfate. The resistance to sulfate attack of modern sprayed concretes produced with non-alkali aluminate-based accelerators in combination with different cement types is related to their microstructure, transport properties, porosity and phase composition. A characterization of these properties allows a comprehensive assessment of the sulfate resistance of shotcrete with the identification of the relevant physical and chemical influencing factors. As with conventional concrete, the cement type and the water to binder ratio are also decisive for the sulfate resistance in shotcrete. On the one hand, capillary porosity and diffusion coefficient show cement-specific differences, and accordingly the sulfate solution uptake and the sulfur profile in the test specimen with cement type and w/b also are different. On the other hand, the type of cement defines the potential for ettringite formation and thus for damage to the concrete. Sulfate expansion is caused by the conversion of monocarbonate/hemicarbonate/monosulfate (AFm phases) to ettringite. The application of sulfate-resistant cements does not guarantee the sulfate resistance of sprayed concretes in each case. Their use, however, minimizes the damage potential. In the sulfate resistance tests, damage in shotcrete causing a drop in the dynamic modulus of elasticity occurs at a higher sulfate expansion compared to conventional concrete due to the higher volume of hardened cement paste and the smaller maximum aggregate size. The studied alkali-free accelerators, currently used in practice, are found to have no direct adverse effect on the sulfate resistance in the dosage investigated and behave more favorably than the aluminate based alkali-containing accelerators. However, the accelerators influence the sulfate resistance indirectly by causing higher porosity and permeability and thus by an increased sulfate solution uptake of the shotcrete.